Synthesis and Characterization of Poly-8-Methylamino-Adenylic. - Elekwa, Iheanyichukwu (Obafemi Awolowo University, 2014)
A polynucleotide, poly-8-methylamino adenylic acid, was synthesized and hybridized with poly U. Adenosine-5-monophosphate purchased from BDN Chemical Corporation was brominated with bromine in Na-acetate buffer pH 3.9, stirred for 24 hours. The excess bromine was removed with some drops of concentrated sodium sulphite solution. It was then evaporated to dryness, on a rotatory evaporator at 37 oC and characterised. The product 8-Bromo-adenosine-5-Monphosphate, was methylaminated with methylamine in water, and refluxed for 48 hours at 65oC on an oil bath. Excess methylamine was removed with dilute sulphuric acid, while the product was evaporated to dryness and characterized.